2014
DOI: 10.1016/j.cub.2014.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Tension and Force-Resistant Attachment Are Essential for Myofibrillogenesis in Drosophila Flight Muscle

Abstract: Our results demonstrate that force-resistant attachment enables a stark tension increase in the myotendinous system. Subsequently, this tension increase triggers simultaneous myofibril self-assembly throughout the entire muscle fiber. As myofibril and sarcomeric architecture as well as their molecular components are evolutionarily conserved, we propose a similar tension-based mechanism to regulate myofibrillogenesis in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
162
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(185 citation statements)
references
References 54 publications
13
162
0
Order By: Relevance
“…One possibility is that Kon helps to localize integrins at the MTJ. In fact, it has been shown that Kon helps to localize integrins at the MTJ in adult flight muscles (Weitkunat et al, 2014), although this is not the case in adult abdominal muscles (Perez-Moreno et al, 2014). Here, we have found that Kon does not regulate αPS2βPS integrin localization at the MTJ in Drosophila embryos.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…One possibility is that Kon helps to localize integrins at the MTJ. In fact, it has been shown that Kon helps to localize integrins at the MTJ in adult flight muscles (Weitkunat et al, 2014), although this is not the case in adult abdominal muscles (Perez-Moreno et al, 2014). Here, we have found that Kon does not regulate αPS2βPS integrin localization at the MTJ in Drosophila embryos.…”
Section: Discussionsupporting
confidence: 46%
“…Kon is essential for the targeting and adhesion between embryonic muscles and tendons (Estrada et al, 2007;Schnorrer et al, 2007), both in the embryo and in the adult (Perez-Moreno et al, 2014;Weitkunat et al, 2014). The molecular nature of Kon and its vertebrate ortholog CSPG4, together with some experimental data, indicates that they function as ECM receptors (Couchman, 2010;Staub et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Through these interactions, obscurin can potentially be linked to a receptor tyrosine kinase (RTK) pathway involved in myogenesis. Obscurin and Kettin are present at an early stage in the development of pupal IFM (Katzemich et al, 2012;Weitkunat et al, 2014). Both are large titin-like proteins with tandem Ig domains, which have a dual function in myogenesis and in the mature muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These premyofibrils subsequently exchange their nonmuscle myosin II for muscle myosin II and extend throughout the fiber (Sparrow and Schock 2009). A recent study in Drosophila has highlighted the importance of mechanical tension, generated through the attachment of the growing muscle fibers to tendons, in the assembly of sarcomeres (Weitkunat et al 2014). We see no evidence of defects in the vertical myosepta to which skeletal muscle fibers attach, nor of a failure of attachment of the fast-twitch fibers, arguing against this being a primary cause of myofibrillogenesis failure in fro mutants.…”
Section: Discussionmentioning
confidence: 99%